2017
DOI: 10.1186/s40645-017-0119-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen mobility in transition zone silicates

Abstract: We study the hydrogen mobility in ringwoodite and wadsleyite considering multiple charge-balanced defects, including Mg < = > 2H, Si < = > Mg + 2H, and the hydrogarnet defect, Si < = > 4H, using molecular dynamics simulations based on the density functional theory at transition zone pressures and temperatures between 1500 and 2500 K. We determine the diffusion coefficients and study in detail the mechanism of hydrogen mobility during lengthy simulations. Our results show that temperature, water concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
5
13
0
Order By: Relevance
“…The diffusivity of hydrogen in solid wadsleyite and ringwoodite has been estimated to range from~10 −10 -10 −5 m 2 /s at the temperature/pressure conditions of the lower mantle of Mars or Earth's transition zone (e.g., Bercovici & Karato, 2003). Figure S1 in the supporting information illustrates that recent simulations (Caracas & Panero, 2017) and experiments (Hae et al, 2006;Sun et al, 2015) favor values toward the middle of this range, for example,~10 −8 -10 −7 m 2 /s. However, partial melting of the basal mantle may speed the transport of hydrogen through the LMBL.…”
Section: Hydrogen Partitions Across the Cmbmentioning
confidence: 95%
“…The diffusivity of hydrogen in solid wadsleyite and ringwoodite has been estimated to range from~10 −10 -10 −5 m 2 /s at the temperature/pressure conditions of the lower mantle of Mars or Earth's transition zone (e.g., Bercovici & Karato, 2003). Figure S1 in the supporting information illustrates that recent simulations (Caracas & Panero, 2017) and experiments (Hae et al, 2006;Sun et al, 2015) favor values toward the middle of this range, for example,~10 −8 -10 −7 m 2 /s. However, partial melting of the basal mantle may speed the transport of hydrogen through the LMBL.…”
Section: Hydrogen Partitions Across the Cmbmentioning
confidence: 95%
“…Although hydrogen entering ringwoodite lattice can significantly enhance diffusion rate, water bonding mechanism and diffusion mechanism remain controversial. Theoretical studies of the defect formation energies from the first principle calculation (Blanchard et al, , ; Caracas & Panero, ) showed that multiple defect incorporation mechanisms could be identified in ringwoodite, dominated by Mg ↔ 2H (i.e., [V Mg (OH) 2 ] X ) at M site and hydrogarnet defect Si ↔ 4H (i.e., [V Si (OH) 4 ] X ) at T site, and minor amount of Si ↔ Mg + 2H (i.e., [Mg Si (OH) 2 ] X ) (Blanchard et al, , ; Caracas & Panero, ). Though Purevjav et al () demonstrated that both tetrahedral and octahedral sites can be simultaneously hydrated in hydrous ringwoodite, infrared spectra of ringwoodite in this study favor the Mg site as hydrogen priority incorporation position.…”
Section: Discussionmentioning
confidence: 99%
“…A recent experimental study demonstrated that the mobility of hydroxyl defects related to a vacant Mg‐octahedron at the M site in ringwoodite is higher than that related to a vacant Si‐tetrahedron at the T site (Mrosko et al, ). Furthermore, molecular dynamics simulations also showed that the greatest H diffusion rate was yielded by Mg ↔ 2H, followed by Si ↔ Mg + 2H, and slowest rate by hydrogarnet defect Si↔4H (Caracas & Panero, ). Thus, one would expect [(2H) x Me ] to be the main diffusing species during diffusion process.…”
Section: Discussionmentioning
confidence: 99%
“…These different characteristics of diffusion response to water may be related to the hydrogen incorporation mechanism in host minerals. Experimental observations (Purevjav et al, 2016;Zhang et al, 2021) and theoretical calculations (Wright and Catlow, 1996;Caracas and Panero, 2017) demonstrated that, for Fe-free hydrous wadsleyite, all hydrogen cations in the crystal should have been fully concentrated into a vacant M3 octahedral sites bonded with oxygen O1. In the case of Fe-bearing hydrous wadsleyite, reduction from ferric to ferrous iron probably drives the formation of Mg vacancies in wadsleyite, which in turn contributes to Fe-Mg interdiffusion.…”
Section: Ringmentioning
confidence: 99%
“…For example, the effect of water on the electrical conductivity of olivine is often contradictory between different groups (D. Yoshino et al, 2006;Karato and Dai, 2009;, 2013Gardés et al, 2015;Dai and Karato, 2015). With respect to the causes of these experimental discrepancies or controversies, one has to fingerprint the type of defect that is involved in each process (from fast electrical conductivity properties to extremely slow rheological processes) (e.g., Berry et al, 2005;Walker et al, 2007;Purevjav et al, 2014Purevjav et al, , 2016Caracas and Panero, 2017;Padrón-Navarta and Hermann, 2017;Tollan et al, 2017Tollan et al, , 2018Le Losq et al, 2019). All these processes related to physical properties of NAMs cannot be the consequence of a single defect.…”
Section: Introductionmentioning
confidence: 99%